Inflation as a global phenomenon: Some implications for policy analysis and forecasting - Ayşe Kabukçuoğlu; Enrique Martínez-García (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
We evaluate the performance of inflation forecasts based on the open-economy Phillips curve by exploiting the spatial pattern of international propagation of inflation. We model these spatial linkages using global inflation and either domestic slack or oil price fluctuations, motivated by a novel interpretation of the forecasting implications of the workhorse open-economy New Keynesian model (Martínez-García and Wynne (2010), Kabukcuoglu and Martínez-García (2014)). We find that incorporating spatial interactions yields significantly more accurate forecasts of local inflation in 14 advanced countries (including the U.S.) than a simple autoregressive model that captures only the temporal dimension of the inflation dynamics.
Keywords: C21; C23; C53; F41; F62; 330; Inflation Dynamics; Open-Economy Phillips Curve; Forecasting